Escama de tilápia-do-Nilo: composição mineral, quantificação da hidroxiapatita de cálcio e caracterização de carbonato de cálcio do precipitado bruto - Santos, Leonardo Bidoia dos (2016)
The high consumption of fish has caused concern in the environmental sector due to the large amount of waste generated, as example the scales. These consist mainly of organic matter, collagen, and an inorganic matrix, called hydroxyapatite which can be natural source of calcium. The aim of this work was to evaluate the mineral composition, the quantification of calcium hydroxyapatite and develop a protocol for precipitation and characterization of calcium carbonate from the Nile tilapia scales (Oreochromis niloticus), from the fish processing industry. For quantification of mineral composition of crude scales, used a technique of atomic emission spectrometry with inductively coupled plasma source, brand, model Shimadzu ICPE-9000®. The quantification of calcium hydroxyapatite was held by x-ray fluorescence (XRF), EDX-7000® model. In the protocol of precipitation evaluated the best concentration of Na2CO3 and ideal pH, using a factorial (3 x 4), were the CaCO3 concentrations in 1, 5 and 10% (m/v) and pH values (7. 0; 8.0; 9.0 and 10.0) in constant temperature to 25°C with ten repetitions, in 95% confidence interval. For the characterization of the precipitate the analytical parameters were determination of the solubility and mineral makeup. The mineral composition of the gross mass of the precipitate was determined by XRF then held the stoichiometric calculation for the quantification of CaCO3 content. Assigned to different conditions of precipitation when used 1% Na2CO3 and pH 9.0 (P1), 1% Na2CO3 and pH 10.0 (P2), 5% of Na2CO3 and pH 9.0 (P3), 5% of Na2CO3 and pH 10.0 (P4). Crude scales submitted mostly in its composition the levels of calcium and phosphorus in the respective values of 116.85 and 60.93g kg-1. The average grade calculated as hydroxyapatite in crude scales was 98.81%. In the determination of the mass of the precipitate, there was no interaction between the levels of Na2CO3 and pH values (P = 0.73). The different concentrations of Na2CO3 influenced (P ˂ 0.01) in the formation of the gross mass of the precipitate, thus the formation of the crude precipitate was higher when used the levels 1 and 5% than 10%. The pH also presented significant differences between them (P ˂ 0.001), showing greater effect in obtaining the precipitate at pH 9.0 and 10.0 gross when compared to pH 7.0 and 8.0. In the solubility of Ca2+ concentration in pH 2.0; 3.0; 4.0; 5.0 and 6.0 were respectively 58.910; 13.401; 1.589; 0.995; 0.778g L-1 what means soluble in acid medium. On the mineral composition of the gross precipitate the predominant elements are the calcium and phosphorus. There was significant difference (P = 0.003) between the precipitation conditions P1, P2, P3 and P4. Contents of CaCO3 were superior in P3 and P4, with respective average values 77.53 and 84.94% compared to P1 and P2. This protocol enabled the precipitation of CaCO3 crude obtained from scales of Nile tilapia, as prospect of source of raw material in the making of toothpastes and calcium repositories relevant to the pharmaceutical industry.